Performance of N,O-Carboxymethyl Chitosan as Corrosion and Scale Inhibitors in CO2 Saturated Brine Solution - Muhamad Jalil Baari; Bunbun Bundjali; Deana Wahyuningrum (Universitas Gadjah Mada, 2021)
The presence of salts and dissolved gas like CO2 that is carried with natural gas and crude oil along the pipeline is the main reason for corrosion and scale formation. These problems are usually resolved separately by corrosion inhibitors and scale inhibitors or acidification. Meanwhile, utilizing a compound to resolve both corrosion and scale formation has an advantage in the economic side and working time. N,O-carboxymethyl chitosan or N,O-CMCs is one of the chitosan's derivates. It is water-soluble and has different functional groups. Those properties support its capability as a complexing agent on corrosion and scale inhibitors. Synthesis of N,O-CMCs was carried out by chemical reactions between chitosan and chloroacetic acid under alkaline circumstances. N,O-CMCs product was characterized using FT-IR and 1H-NMR spectroscopy. The inhibition efficiency was analyzed by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization techniques. The measurements showed that the highest efficiency of corrosion inhibition reached 63.54% when the concentration and temperature were 30 ppm and 35 °C, respectively. N,O-CMCs was classified as a mixed-type inhibitor. The adsorption mechanism of the inhibitor followed Langmuir adsorption isotherm. The static scale inhibition test informed that the optimum inhibition efficiency of N,O-CMCs reached 60.00%.